Adrenomedullin: new inhibitory regulator for cortisol synthesis and secretion. Issue 1 (8th September 2021) - Travers, Simon; Martinerie, Laetitia; Xue, Qiong-Yao; Perrot, Julie; Viengchareun, Say; Caron, Kathleen M; Blakeney, Elizabeth S; Boileau, Pascal; Lombès, Marc; Pussard, Eric
Abstract : Preterm birth is associated with immaturity of several crucial physiological functions notably those prevailing in the lung and kidney. Recently, a steroid secretion deficiency was identified in very preterm neonates, associated with a partial yet transient deficiency in 11β-hydroxylase activity, sustaining cortisol synthesis. However, the P450c11β enzyme is expressed in preterm adrenal glands, we hypothesized an inhibition of cortisol production by adrenomedullin (ADM), a peptide highly produced in neonates and whose effect on steroidogenesis remains poorly known. We studied the effects of ADM on three models: 104 cord-blood samples of the PREMALDO neonate cohort, genetically targeted mice overexpressing ADM, and two human adrenocortical cell lines (H295R and HAC15 cells). Mid-regional-proADM (MR-proADM) quantification in cord-blood samples showed strong negative correlation with gestational age ( P = 0.0004), cortisol production ( P < 0.0001), and 11β-hydroxylase activity index ( P < 0.0001). Mean MR-proADM was higher in very preterm than in term neonates (1.12 vs 0.60 nmol/L, P < 0.0001). ADM-overexpression mice revealed a lower 11β-hydroxylase activity index ( P < 0.05). Otherwise, aldosterone levels measured by LC-MS/MS were higher in ADM-overexpression mice (0.83 vs 0.46 ng/mL, P < 0.05). More importantly, the negative relationship between adrenal ADM expression and aldosterone production found in control was lacking in the ADM-overexpression mice. Finally, LC-MS/MS and gene expression studies on H295R and HAC15 cells revealed an ADM-induced inhibition of both cortisol secretion in cell supernatants and CYP11B1 expression. Collectively, our results converge toward an inhibitory effect of ADM on glucocorticoid synthesis in humans and should be considered to explain the steroid secretion deficiency observed at birth in premature newborns.